DETERMINANT OF THE QUALITY OF REGIONAL FINANCIAL REPORTS - Zaelika Fatmawati M; Entar Sutisman; Sumartono; Suratini; La Ode Marihi (Universitas Yapis Papua, 2021)
This review was directed to look at and investigate the impact of inside control frameworks, bookkeeping data frameworks, monetary management and the utilization of data innovation on the nature of the budget summaries of the Jayapura City Government OPD. The number of inhabitants in this exploration is all Regional Apparatus Organizations in Jayapura City, adding up to 34 offices. In light of the purposive testing procedure, an example of 102 individuals was acquired from each territorial association. The investigation procedure utilized is various straight relapse. Then, at that point, the consequences of the review show that: (1) The Internal Control System has a positive and critical impact on the Quality of Financial Reports. (2) The Regional Financial Accounting System has a positive and critical impact on the Quality of Financial Reports. (3) Financial Supervision doesn't influence the Quality of Financial Reports. (4) Utilization of Information Technology doesn't influence the Quality of Financial Reports. (5) Internal Control System, Regional Financial Accounting System, Financial Supervision, and Utilization of Information Technology have a critical concurrent impact on the Quality of Financial Reports